Building Capacity for Mortality Statistics Programs: Perspectives from the Indonesian Experience - Chalapati Rao; Yuslely Usman; Matthew Kelly; Trijuni Angkasawati; Soewarta Kosen (Springer, 2019)
Information on deaths by age, sex, and cause are primary inputs for health policy and epidemiological research. Currently, most developing countries lack efficient death registration systems that generate these data on a routine and timely basis. The global community is promoting initiatives to establish and strengthen national mortality statistics programs across the developing world. Building human, technical, and institutional capacity to operate these programs are essential elements for the program. In Indonesia, the government has established a national Sample Registration System (SRS) covering a population of 9 million and is looking toward further scaling up of operations of the mortality statistics program in conjunction with expansion of the national Civil Registration and Vital Statistics (CRVS) systems. This article reports the theoretical and practical perspectives gained from experiences in developing human capacity in the Indonesian context. These perspectives are described in terms of the institutional, personnel, and functional components of the program for collection, compilation, analysis, and utilisation of mortality and cause of death data. The article also describes the challenges and potential solutions for implementing capacity building activities at national and subnational level. In conclusion, the need for and availability of training resources are discussed, including the potential for involvement of public health academia and international collaborations within a research framework on program management, quality evaluation, and data utilisation. Adequate attention to capacity building is essential to ensure the success and sustainability of national mortality statistics programs.